Pedal Curves of Tangent Surfaces of Biharmonic B-General Helices according to Bishop Frame in Heisenberg Group Heis - Korpinar, Talat; Turhan, Essin (Soc Paranaense Matematica, 2014)
In this paper, we study pedal curves of tangent surfaces of biharmonic B-general helices according to Bishop frame in the Heisenberg group Heis. We give necessary and sufficient conditions for B-general helices to be biharmonic according to Bishop frame. We characterize this pedal curves in the Heisenberg group Heis(3). Additionally, we illustrate our main theorem.
Keywords: Biharmonic curve; Bishop frame; Heisenberg group; Pedal curve